PENGEMBANGAN FLIPBOOK DIGITAL BERBASIS CANVA PADA MATERI LINGKARAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VIII - Ulul Azmi; Iwit Prihatin; Abdillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to create a Canva-based digital flipbook on circle material to enhance the problem-solving skills of eighth-grade students. The research design used in this Research and Development (R&D) study is the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluating. Based on the research results and discussion, the first is the average of the percentage calculation from material experts and media experts, which is obtained at 94.80% with very valid criteria. The second average from the calculation of the percentage of teacher response questionnaires and student response questionnaires is 88.56% with the criteria of very practical. As for the third, the calculation of the posttest results for students reached an effectiveness level of 66.67% with an effective criterion.